CRISIS MANAGEMENT OF EXCHANGES: THE EXPERIENCE OF FOREIGN COUNTRIES AND THE POSSIBILITY OF APPLICATION IN THE RUSSIAN FEDERATION - Malyshenko, Konstantyn; Malyshenko, Vadim; Fastynova, Viktorii; Mardar, Diana; Boyarchuk, Nadezhda (Revista Inclusiones, 2020)
The purpose of this study is to solve the issues of developing and applying a certain set of measures of stock markets crisis management in the Russian Federation. Thus, the main task is to develop a specific set of methods for crisis management to be used on Russian exchanges. The research is conceptually based on the E. Fama hypothesis of effective markets, as events trigger a crisis as a reaction to their positive (more often, negative) content. The method in its general sense is statistical indicators, and specifically the levels of standard deviation (emissions as a criterion for a crisis situation). The analysis of both the concept of crisis management and of various methodological approaches and measures applied in foreign practice was carried out. Thus, the research resulted in the development of a model for ensuring the liquidity of the Russian Federation's stock market, which is presented as a set of methods of crisis management. Despite the methodological uncertainty of the very term ‘anti-crisis management’ in the works of Russian scientists, the authors note that crisis management is a set of various measures to restore the stable operation of the exchange and its liquidity, which can be compared with measures applied in foreign countries. At the same time, it is necessary to create an individual set of anti-crisis measures for the domestic practice of managing exchanges.